Effect of early laparoscopic Cholecystectomy in Acute Cholecystitis - Ali, Abdulhameed J.; AL-Ogali, Arkan A.; Salih, Hala I.; Turfa, Abdalrahman H. (AL-Kindy College Medical Journal, 2014)
Background: Laparoscopic cholecystectomy (LC) has become the treatment of choice for elective cholecystectomy.Objectives: To evaluate the safety and feasibility of early LC for AC and to compare the results with delayed LC.Methods: A prospective study done from April 2011 to October 2013, 88 patients with diagnosis of AC were divided randomly into two groups according to the mode of treatment; (early group n=40) treated by early LC within first 72 hours or (delayed group, n=48) initial conservative treatment for 4-6 weeks, followed by delayed LC.Results: There was no difference between the two groups (early & delayed LC), operating time (early 80min, delayed70min), conversion rate (early 7.5%, delayed 6.25%),postoperative complications (early 20%, delayed 14.58%),However, the early group had shorter mean hospital stay(early 2.5 days, delay 5 days).Conclusion: early laparoscopic cholecystectomy appears to be reliable, safe, and cost effective treatment modality for acute cholecystitis, offering the additional benefits of a shorter hospital stay.Keywords: Acute cholecystitis, early LC, delayed LC.